2021
DOI: 10.1016/j.dcn.2021.100958
|View full text |Cite
|
Sign up to set email alerts
|

The rise and fall of rapid occipito-temporal sensitivity to letters: Transient specialization through elementary school

Abstract: Letters, foundational units of alphabetic writing systems, are quintessential to human culture. The ability to read, indispensable to perform in today’s society, necessitates a reorganization of visual cortex for fast letter recognition, but the developmental course of this process has not yet been characterized. Here, we show the emergence of visual sensitivity to letters across five electroencephalography measurements from kindergarten and throughout elementary school and relate this development to emerging … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
64
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(72 citation statements)
references
References 81 publications
5
64
3
Order By: Relevance
“…This section largely overlaps with that of our recent report (Fraga-González et al, 2021). EEG data were recorded at 1 kHz sampling rate using an MR-compatible 128-channel EEG system (Net Amps 400, EGI HydroCelGeodesic Sensor Net) during functional magnetic resonance imaging (fMRI) in a Philips Achieva 3T scanner (Philips Medical Systems, Best, The Netherlands).…”
Section: Eeg Data Acquisition and Preprocessingmentioning
confidence: 99%
See 2 more Smart Citations
“…This section largely overlaps with that of our recent report (Fraga-González et al, 2021). EEG data were recorded at 1 kHz sampling rate using an MR-compatible 128-channel EEG system (Net Amps 400, EGI HydroCelGeodesic Sensor Net) during functional magnetic resonance imaging (fMRI) in a Philips Achieva 3T scanner (Philips Medical Systems, Best, The Netherlands).…”
Section: Eeg Data Acquisition and Preprocessingmentioning
confidence: 99%
“…The current study combines longitudinal and cross-sectional samples from a larger group of Germanspeaking children who took part in a large project with simultaneous EEG/fMRI sessions, behavioral tests and a grapheme-phoneme intervention training (Karipidis et al, 2017(Karipidis et al, , 2018Pleisch et al, 2019;Mehringer et al, 2020;Wang et al, 2020;Fraga González et al, 2021). Here, we focus on data from kindergarten (T1), middle of first grade (T2), end of first grade (T3), middle of second grade (T4), and middle of fifth grade (T5) of elementary school.…”
Section: Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…This coarse-grade sensitivity emerges during reading acquisition. Although this is absent in kindergarten children (Maurer et al, 2005b), it emerges after one year of reading instruction (Eberhard-Moscicka et al, 2015;Varga et al, 2020) and follows an inverted U shape pattern which peaks during reading acquisition and then declines over instruction (Fraga-González et al, 2021). The N1 for print is more pronounced over the left posterior-occipital regions (Maurer et al, 2005a;Yoncheva et al, 2010), and this left lateralization is enhanced with reading experience.…”
Section: Introductionmentioning
confidence: 95%
“…According to the phonological mapping hypothesis, the left lateralization is driven by automatized grapheme-phoneme mapping . Typically, children show a bilateral effect for letter strings (Maurer et al, 2006;Kast et al, 2010); however, recent studies found that left lateralization can be found as early as one year (Varga et al, 2020; van de Walle de Ghelcke et al, 2021) or even half a year of reading instruction (Pleisch et al, 2019; altough lateralization is less clear for single letters, see Fraga-González et al, 2021).…”
Section: Introductionmentioning
confidence: 99%